The use of biochemical blood markers for early prediction of the intensity of live weight gain of calves - S. V. Nikolaev (Аграрная наука Евро-Северо-Востока, 2022)
The aim of the research was to identify promising biochemical markers of blood associated with the intensity of live weight gain in young cattle. The work was carried out in 2021...2022 in the conditions of the dairy farm of LLC Severnaya Niva in the Kortkerossky district of the Komi Republic. A group of newborn heifers of the Kholmogorsky breed (n = 30) was selected for the experiment. It has been established that on the first day after birth, calves with intensive growth rates had lower AsAT activity (r = -0.510) and iron concentration (r = -0.650) in blood serum, and vice versa a higher level of SMLMM рlasma (0.626). At later stages of the analysis, a pronounced correlation of the intensity of body weight gain was observed with respect to the activity of alkaline phosphatase: -0.639 and -0.744 on day 7 and 14, respectively. It was determined that many of the calculated coefficients obtained during the blood test on the 14th day after birth had a more noticeable correlation with the intensity of growth. Such markers included: Alkaline phosphatase/Calcium (-0.746), Alkaline phosphatase/Magnesium (-0.756), Magnesium/Alkaline Phosphatase (-0.760), Calcium×Phosphorus/Alkaline Phosphatase (0.758) and Alkaline Phosphatase/(Calcium+Magnesium) (-0.753). At the next stage, the analysis of the rate of live weight gain in heifers ranked by the increase in the values of the developed coefficients was carried out. It is proved that the use of coefficients contributed to a more pronounced differentiation of the rate of weight gain in comparison with the values established with the use of one alkaline phosphatase. Thus, the calculated index of Alkaline phosphatase/Calcium/ Magnesium on the 1st, 7th and 14th days of postnatal ontogenesis provided a difference between the phenotypes of the 1st and 3rd groups by 74.1(P≤0.05), 92.6 (P≤0.01) and 90.7 (P≤0.001) g of weight gain per day, whereas the difference when using one alkaline phosphatase was 33.3; 16.0 and 12.2 % less. Thus, the use of these coefficients to predict the rate of live weight gain in calves can increase the accuracy of the selection of animals with the desired phenotype in early postnatal ontogenesis.